Drivers of adoption and spread of wildlife management initiatives in Mexico. Issue 7 (29th May 2021) - Romero‐de‐Diego, Cristina; Dean, Angela; Jagadish, Arundhati; Witt, Bradd; Mascia, Michael B.; Mills, Morena
Abstract: Conservation initiatives rarely achieve the scale required to respond to ongoing biodiversity loss. Understanding what drives the adoption of conservation initiatives provides key insights into how initiatives expand to a scale necessary for effective conservation outcomes. In this article, we identified characteristics of conservation initiatives, adopters, and context that influenced the adoption of extensive Wildlife Management Units (UMAs) in Mexico. We interviewed 22 experts to gather their perceptions about the factors driving the adoption and spread of UMAs, and their interactions. We used Diffusion of Innovation Theory and qualitative data analysis to develop a theory of change based on the experts' perceptions that illustrates what led landholders to adopt UMAs. We found that: (a) the adoption of UMAs depended on the landholders' ability to learn about, register, and implement them; (b) alignment with the landholders' objectives and private tenure facilitated adoption, reflecting the likelihood and ease of participation, respectively; and (c) observability of benefits and the availability of technical advice were key to adoption, influencing the speed of adoption by facilitating learning. Our empirically derived theory of change describing the adoption of UMAs revealed focused and clear hypotheses that can be further tested quantitatively.